PEMANFAATAN BOTTOM ASH SEBAGAI AGREGAT BUATAN - Nuciferani, Felicia Tria; Antoni, Antoni; Hardjito, Djwantoro (Magister Teknik Sipil Universitas Kristen Petra, 2014)
ABSTRACT: The aim of this study is to explore the possible use of bottom ash as artificial aggregates. It is found that the pelletizer method by using mixer without blade is one possibility to manufacture artificial aggregates. The optimum mixture composition of artificial aggregate is found to be 3 BA : 1FA : 0,5 C , by weight, and immersed once in cement slurry. The water content in ssd condition is 27% with the compressive strength of the aggregate 2.4 MPa on the seventh day. Concrete produced with mixture compositition of 1 cement : 1.5 sand by weight, resulted in water content of 14.63% in ssd condition and compresive strength of 14.20 MPa at 28th day.